Protective effect of Trihoney against Hypercholesterolemia-induced abnormalities in sperm quality parameters. - Hamad Mohamed, Zenab; Hamad Alfarisi, Hamad Abdulsalam; Abdul Wahab, Azantee Yazmie; Abd. Fuaat, Azliana; Che Mohamad, Che Anuar; Ibrahim, Muhammad (2019)
A growing body of evidence has linked hypercholesterolemia with a reduction in the sperm count and motility coupled with an increase in the sperm morphological abnormalities. It affects spermatogenesis, sperm cytoskeleton, epididymal sperm maturation and the sperm fertilizing capacity. Due to claim of various side effects associated with current medical treatment, there have been a growing interest of the public toward the use of herbal medicine. Hence, the aim of this study was to investigate the protective effects of a novel Trihoney on sperm parameters of hypercholesterolemic rabbits.